Educational Reform in Contemporary China: An Autobiographic Ethnographic Study of a Local University in Gansu Province - Tianjin, Wang (Advances in Social Sciences Research Journal, 2022)
This paper reviews the educational reform process in contemporary China based on an autobiographic ethnographic case study of Tianshui Normal University (TNU) in Gansu province. It examines the relationship between Chinese culture and education, probes the modern education model in China, and offers some operational suggestions for further education reforms in China. The author adopted qualitative research methods to study the critical issues related to educational reform in contemporary China and demonstrated the accomplishments of educational reform in China.